A novel water-soluble platinum(II) complex with the amino acid deoxyalliin: synthesis, crystal structure, theoretical studies and investigations about its antibacterial activity - Quintanilha, Mariana Mazzo; Schimitd, Bianca Alves; Costa, Adão Marcos Ferreira; Nakahata, Douglas Hideki; Simoni, Déborah de Alencar; Clavijo, Juan Carlos Tenorio; Pereira, Douglas Henrique; Massabni, Antonio Carlos [UNESP]; Lustri, Wilton Rogério; Corbi, Pedro Paulo (Elsevier, 2021)
Platinum complexes have received special attention due to their biological properties with emphasis on the antitumor and antibacterial activities. In this manuscript, we report the synthesis of a novel water-soluble Pt(II) complex with the amino acid deoxyalliin (S-allyl-L-cysteine, sac), [Pt(sac)2], and its characterization by a set of chemical and spectroscopic techniques besides its preliminary antibacterial activity assays. Elemental and high-resolution mass spectrometric data (ESI-MS) indicated its 1:2 metal/ligand molar composition, with the molecular formula [Pt(C6H10NO2S)2]⋅H2O. The crystal structure of the complex was solved by single-crystal X-ray diffraction studies, where the two molecules of deoxyalliin were shown to be coordinated to the metal in a bidentate N,S-mode and in a trans-configuration. The 1H, 13C and 195Pt nuclear magnetic resonance (NMR) results and the infrared spectroscopic data reinforced the N,S-coordination of deoxyalliin to the metal. The coordination mode of the ligand was supported by density functional theory (DFT) calculations. The antibacterial activity of the complex was preliminarily evaluated by the minimum inhibitory concentration (MIC) assay. The experiments were performed for the complex and the free ligand over Gram-positive (Staphylococcus aureus and Bacillus cereus) and Gram-negative (Escherichia coli and Pseudomonas aeruginosa) bacterial strains. The [Pt(sac)2] complex did not show inhibitory effect in bacterial growth even at the highest concentration of 3.75 mmol L−1 considered in the present study.
Keywords: Antibacterial activity; Crystal structure; Deoxyalliin; DFT studies; Mass spectrometry; Platinum(II)